2020
DOI: 10.1002/cpch.83
|View full text |Cite
|
Sign up to set email alerts
|

1D 1H NMR as a Tool for Fecal Metabolomics

Abstract: Metabolomic studies allow a deeper understanding of the processes of a given ecological community than nucleic acid–based surveys alone. In the case of the gut microbiota, a metabolic profile of, for example, a fecal sample provides details about the function and interactions within the distal region of the gastrointestinal tract, and such a profile can be generated in a number of different ways. This unit elaborates on the use of 1D 1H NMR spectroscopy as a commonly used method to characterize small‐molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Human fecal matter is a waste product of food digestion and mainly contains water, undigested food remnants, including nitrogen and protein matter, carbohydrates, lipids, and hundreds of small molecular metabolites, as well as bacteria [1]. Fecal matter is also a rich source of metabolic information and the noninvasive sampling has increased interest toward exploring the human fecal metabolome as a function of diet, diseases, and other lifestyle conditions [1,2]. Recent studies have shown close relationships between the dynamics of the fecal metabolome and gut microbiome functions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Human fecal matter is a waste product of food digestion and mainly contains water, undigested food remnants, including nitrogen and protein matter, carbohydrates, lipids, and hundreds of small molecular metabolites, as well as bacteria [1]. Fecal matter is also a rich source of metabolic information and the noninvasive sampling has increased interest toward exploring the human fecal metabolome as a function of diet, diseases, and other lifestyle conditions [1,2]. Recent studies have shown close relationships between the dynamics of the fecal metabolome and gut microbiome functions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Aliquots of cecal fluid were serially centrifuged, and the supernatant was passed through a 0.22 uM filter and stored at −80 °C for future metabolite analysis. Fecal material underwent the same process, with the exception of the collection and vessel establishment samples (0 h), which were first diluted at 25% wt/vol [ 22 ] with sterile phosphate-buffered saline (PBS) and vigorously mixed prior to centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Filtered supernatant samples for metabolite analysis were standardized through the addition of a DSS-d6 Chenomx Internal Standard (Chenomx, EDM, CAN). Samples were read on a nuclear magnetic resonance (NMR) spectrometer with an operating field of ≥600 MHz using the METNOESY sequence [ 22 ] at the University of Guelph Advanced Analysis Center. Sample pH was measured using Cytiva Whatman wide-range pH indicator strips (Fisher Scientific, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was scanned at 298K in a Bruker Avance III 600 MHz spectrometer with a 5 mm TCI 600 cryoprobe (Bruker, Billerica, MA, USA) at the Advanced Analysis Centre in the University of Guelph, ON, Canada according to (8), except the number of scans was increased from 32 to 1536 to increase sensitivity for the low concentration fecal filtrate samples. Sample spectra were processed and analyzed at the Advanced Analysis Centre in the University of Guelph in Chenomx NMR suite 9.0 according to (8) with 128K zero filling and 0.2 Hz line broadening. Targeted metabolite concentrations were determined by the best fit for the peak regions within the Chenomx library of compounds.…”
Section: Supplementary Figures 12mentioning
confidence: 99%